2016
DOI: 10.1080/10826084.2016.1233983
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Direction of Effect of Alcohol Problems and Internalizing Symptoms in a Longitudinal Sample of College Students

Abstract: Background Alcohol problems and internalising symptoms are consistently found to be associated but how they relate to each other is unclear. Objective The present study aimed to address limitations in the literature of comorbidity of alcohol problems and internalising symptoms by investigating the direction of effect between the phenotypes and possible gender differences in college students. Method We utilised data from a large longitudinal study of college students from the United States (N=2607). Three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Substance use was another statistically significant predictor of internalizing behaviors in our study. This finding is consistent with Homman et al’s (2017) recent research with students. It is possible that some students tend to cope with life and academic stressors by smoking and consuming alcohol (Churakova et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Substance use was another statistically significant predictor of internalizing behaviors in our study. This finding is consistent with Homman et al’s (2017) recent research with students. It is possible that some students tend to cope with life and academic stressors by smoking and consuming alcohol (Churakova et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…Although these conditions often co-occur developmentally, internalizing symptoms can be detected as early as age 3 (Burlaka et al, 2015) while substance use typically begins around adolescent age (Burlaka, 2017; Kessler, 2004). However, Homman et al (2017) found that for male students, alcohol problems first predicted internalizing problems and then internalizing problems would predict alcohol problems, whereas for female college students, a unidirectional relationship was found with alcohol problems predicting internalizing behavior problems.…”
mentioning
confidence: 87%
See 1 more Smart Citation